A new and critically endangered species of Polylepis (Rosaceae) from the central Andes of Peru - Quispe-Melgar, Harold Rusbelth; Llacua-Tineo, Yashira Stefani; Huayta-Hinojosa, L. David; Cruz, Marleny Prada De La; Kessler, Michael (Phytotaxa, 2026)
We describe and illustrate a new species of Polylepis endemic to the departments of Huancavelica and Ayacucho, Peru. It is most similar to P. occidentalis, but differs in having the lower leaflet surface and rachis densely lanate (vs. densely tomentose); stipular sheaths apically truncate (vs. apically acute and spurred); inflorescences bearing 3–8 flowers (vs. 4–12); sepals 3–5 (vs. 4); stamens 30–40 per flower (vs. 9–15); and densely lanate fruits (vs. densely villous). The species appears to be rare and narrowly distributed, suggesting that it may be critically endangered and in urgent need of conservation attention.